Research progress on Nrf2 intervention in the treatment of diabetic retinopathy - Yang, Yuchen; Zou, Haidong (Frontiers in Endocrinology, 2025)
Diabetic retinopathy (DR) is a primary cause of vision loss among individuals with diabetes and represents the most prevalent microvascular complication of diabetes mellitus. Its pathophysiological mechanisms involve processes such as oxidative stress, chronic inflammation, cell apoptosis, and angiogenesis. As a core transcription factor in the antioxidant response, Nrf2 upregulates the expression of antioxidant genes through the Keap1-Nrf2-ARE pathway, hence reducing reactive oxygen species (ROS) levels in retinal cells and alleviating oxidative stress and correlated damage. By activating Nrf2, the release of pro-inflammatory cytokines is inhibited, which helps mitigate inflammation and delays DR progression through anti-apoptotic effects, suppression of angiogenesis and ferroptosis inhibition. This review highlights the Nrf2-related regulatory mechanisms and the latest research progress regarding its function in DR, offering a theoretical foundation for Nrf2-targeted DR therapies.